2008
DOI: 10.1136/ard.2006.064931
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bone remodelling and antifracture efficacy of intermittent bisphosphonate therapy: implications from clinical studies with ibandronate

Abstract: Bisphosphonates reduce the rate of bone resorption and bone remodelling. Given daily, they decrease the risk of fractures in postmenopausal osteoporosis. When bisphosphonates were given at extended drug-free intervals this antifracture efficacy was generally not seen. This may be due to the different pattern of bone remodelling changes. Data from randomised clinical studies of ibandronate, given orally or intravenously, at different doses and for variable time intervals to women with osteoporosis were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 67 publications
1
18
0
1
Order By: Relevance
“…The effect of hPTH (1-34) on hip fracture reduction has not been shown in clinical studies in GIOP populations. [55, 57]. In our current study, we found GCs reduced vertebral bone strength, an observation that is consistent with bone loss [35, 41].…”
Section: Discussionsupporting
confidence: 88%
“…The effect of hPTH (1-34) on hip fracture reduction has not been shown in clinical studies in GIOP populations. [55, 57]. In our current study, we found GCs reduced vertebral bone strength, an observation that is consistent with bone loss [35, 41].…”
Section: Discussionsupporting
confidence: 88%
“…3 However, as BPs reside in bone for a long time, daily, weekly, or even monthly administration should have similar efficacy, provided the cumulative doses are similar. This has been described for ibandronate and zoledronate when administration frequency is prolonged 11. During the period of treatment with BPs, bone resorption does not become progressively lower but reaches a new steady-state level, suggesting that, despite accumulation of BPs in the skeleton, bone turnover still continues, albeit at a slower rate.…”
Section: Pharmacokinetics Of Bisphosphonates (Bps)mentioning
confidence: 74%
“…At the end of 60 months of continuous treatment, median sP1NP values were 57% and 45% lower than at DIVA core baseline, i.e., within the premenopausal range. Although no further reductions in biomarker levels were observed from DIVA core, biomarker levels remained within the premenopausal range [16,17] throughout the study and, therefore, remained clinically relevant in terms of responsiveness to treatment [22].…”
Section: Discussionmentioning
confidence: 96%